2016
DOI: 10.1242/dev.134577
|View full text |Cite
|
Sign up to set email alerts
|

Golgb1 regulates protein glycosylation and is crucial for mammalian palate development

Abstract: Cleft palate is a common major birth defect for which currently known causes account for less than 30% of pathology in humans. In this study, we carried out mutagenesis screening in mice to identify new regulators of palatogenesis. Through genetic linkage mapping and whole exome sequencing, we identified a loss-of-function mutation in the Golgb1 gene that co-segregated with cleft palate in a new mutant mouse line. Golgb1 encodes a ubiquitously expressed large coiled-coil protein, known as giantin, that is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 75 publications
(96 reference statements)
2
86
1
Order By: Relevance
“…Since Golga5 is structurally closely related to Golgb1 and since we recently showed that mice lacking Golgb1 survive to birth and exhibit specific craniofacial developmental defects (Lan et al 2016), we investigated whether the lack of obvious developmental defects in Golga5 -deficient mice is due to functional complementation by Golgb1. We crossed Golga5 E3-4del/E3-4del homozygous female mice with Golgb1 E13-25bp/+ male mice, which are heterozygous for a 25-bp deletion in exon-13 of the Golgb1 gene that causes complete loss of Golgb1 function (Lan et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since Golga5 is structurally closely related to Golgb1 and since we recently showed that mice lacking Golgb1 survive to birth and exhibit specific craniofacial developmental defects (Lan et al 2016), we investigated whether the lack of obvious developmental defects in Golga5 -deficient mice is due to functional complementation by Golgb1. We crossed Golga5 E3-4del/E3-4del homozygous female mice with Golgb1 E13-25bp/+ male mice, which are heterozygous for a 25-bp deletion in exon-13 of the Golgb1 gene that causes complete loss of Golgb1 function (Lan et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We crossed Golga5 E3-4del/E3-4del homozygous female mice with Golgb1 E13-25bp/+ male mice, which are heterozygous for a 25-bp deletion in exon-13 of the Golgb1 gene that causes complete loss of Golgb1 function (Lan et al 2016). We then crossed Golga5 E3-4del/+ Golgb1 E13-25bp/+ double heterozygous progeny with Golga5 E3-4del/E3-4del homozygous mice and found that the Golga5 E3-4del/E3-4del Golgb1 E13-25bp/+ mice (n=15) survive postnatally without obvious developmental abnormality and behaved similarly as the Golga5 E3-4del/E3-4del and Golga5 E3-4del/+ Golgb1 E13-25bp/+ littermates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Freshly dissected maxillary explants of E13.5 embryos were cultured as described previously by Lan et al (Lan, Zhang et al 2016). …”
Section: Roller Bottle Culture For Maxillary Explantsmentioning
confidence: 99%